Molecular Determinants of the Interaction between Coxsackievirus Protein 3A and Guanine Nucleotide Exchange Factor GBF1 - Wessels, Els (American Society for Microbiology, 2007)
The 3A protein of coxsackievirus B3 (CVB3), a small membrane protein that forms homodimers, inhibits endoplasmic reticulum-to-Golgi complex transport. Recently, we described the underlying mechanism by showing that the CVB3 3A protein binds to and inhibits the function of GBF1, a guanine nucleotide exchange factor for ADP-ribosylation factor 1 (Arf1), thereby interfering with Arf1-mediated COP-I recruitment. This study was undertaken to gain more insight into the molecular determinants underlying the interaction between 3A and GBF1. Here we show that 3A mutants that have lost the ability to dimerize are no longer able to bind to GBF1 and trap it on membranes. Moreover, we identify a conserved region in the N terminus of 3A that is crucial for GBF1 binding but not for 3A dimerization. Analysis of the binding domain in GBF1 showed that the extreme N terminus, the dimerization/cyclophilin binding domain, and the homology upstream of Sec7 domain are required for the interaction with 3A. In contrast to that of full-length GBF1, overexpression of a GBF1 mutant lacking its extreme N terminus failed to rescue the effects of 3A. Together, these data provide insight into the molecular requirements of the interaction between 3A and GBF1.